OP0317 Screening of an autoantibody signature of early knee osteoarthritis: data from the osteoarthritis initiative. (12th June 2018) - Camacho Encina, M.; Calamia, V.; Picchi, F.; VanDuin, J.; Qiu, J.; Ruiz Romero, C.; LaBaer, J.; Blanco, F.J.
Abstract : Background: The immune system can detect the changes involved in the osteoarthitic (OA) joint, triggering the production of immunoglobulins against self-proteins (Autoantibodies or AAbs). As AAbs might be generated in a stage prior to the disease, they can be potentially used to identify an increased risk for the disorder, allowing the diagnosis of asymptomatic OA. Objectives: The discovery of an AAb signature useful for the early diagnosis of knee OA. Methods: Nucleic Acid-Programmable Protein Arrays (NAPPA) were used to screen the presence of AAbs against 2200 human proteins in sera belonging to two different subcohorts from the Osteoarthritis Initiative (OAI): Incidence and Non-exposed subcohorts. Participants in the incidence subcohort had not developed any symptomatic knee OA at baseline, but they did present an increased risk of developing the disease. Non-exposed subcohort incorporate participants which have no radiographic findings or symptoms of knee OA, nor any reported risk factors. A hundred sera from both subcohorts at baseline were used. In order to know if the profile of AAbs was specific of asymptomatic OA, samples belonging to the same patients selected from the incidence subcohort were analysed after 72 months of follow up, when all of them have developed OA. Data were normalised following the Biodesing Institute criteria. A 1.1 cutoff was used to determine reactivity and all proteins over the cutoff were analysed by Wilcoxon test. The Partial Area Under the Curve (pAUC) at 95% specificity was analysed with a p value<0.05. Results: We detect AAbs against six proteins showing different reactivity (see table 1) in a stage prior to the disease –samples from the incidence subcohort at baseline compared with the non-exposed subcohort–. These proteins were implicated in the colesterol biosynthesis (Diphosphomevalonate decarboxylase, MVD), and the elimination of pottentially toxic xenobiotic or endogenous compounds (ASB7 and UGT1A7, repectively). We also found a GTPase from the Rho family (RAC3), the Vacuolar protein sorting-associated protein 4B (VPS4B), which has been recently reported to facilitate chondrocyte apoptosis in a OA rat model, and Methionine adenosyltransferase 2 subunit beta (MAT2B). The latter is the regulatory subunit of the enzyme responsible of the catalysis of S-adenosylmethionine, a dietary supplement widely used in the management of OA symptoms. None of the six AAbs were found after the disease has been established (samples from the incidence subcohort at 72 months). Conclusions: This work is the first to screen a large number of human proteins for the discovery of OA-associated AAbs. We define a panel of six AAbs, which are increased prior to the development of symptomatic knee OA. These results suggest that a serum AAbs signature can facilitate the discovery of early OA biomarkers useful for clinical diagnosis. Acknowledgements: This work has received financial support from the Xunta de Galicia and the European Union (European Social Fund – ESF). Disclosure of Interest: None declared